Chagas abertas, coração feliz: travessias dos pagadores de promessas de Juazeiro do Norte - Walsh Netto, Patrick (2008)
This ethnographic work intends to analyze the religious phenomena of Juazeiro do Norte under three propositions: the social types of the promise payers, the kinds of their promises and the background of this scenario, made of a moisture of pain and joy, the both integrant parts of the crossings in asking of grace, the grace achievement and the grace’s retribution. The results of this field research are put on discussion depart from the concept of gift, just like employed by Marcel Mauss, and also with a dialogue with Max Weber, wanting the construction of ideal types of pilgrims, promise payers and their various requests. In resume, this work have no intention to rise deep rooted hypothesis, because is an ethnographical research that suggest to think about the bundle of lines of intensity that crosses these social actors.